PENGARUH JENIS PUPUK TERHADAP PRODUKSI DAUN TEMBAKAU(Nicotiana tabacum) - Tyas Soemarah K.D; Teguh Supriyadi; Endang Suprapti; Haryuni (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
One effort to increase tobacco production and productivity on dry land is by fertilizing. Fertilization is a plant maintenance activity that aims to improve soil fertility. Fertilizers commonly used by farmers for tobacco plants namely organic (manure) and inorganic include ZA, ZK, NPK and SP36 if needed.This study aims to determine the effect of each fertilizer on plant growth. This research was conducted in Plosorejo Village, Randublatung District, Blora Regency, at an altitude of 210 meters above sea level. The type of soil in the research location is Grumosol (soil which is slightly calcareous and easily erosion or landslide).The method used in the study was a Randomyzed Complete Block Design (RCBD) with a single and 5-level treatment / level with 5 replications. The treatments used were administration of NPK Phonska Fertilizer (P1), NPK Fertilla Fertilizer (P2), NPK Fertilla + ZA (P3), NPK Fertilla + ZK (P4) Fertilizer and ZA + ZK Fertilizer (P5).The results of the five treatments showed that the highest amount of heavy leaf production was found in treatment P3 (Non Chlor NPK and ZA fertilizer).